2022
DOI: 10.21203/rs.3.rs-1973901/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversity, Abundance and Distribution of Avifauna in District Jhang, Pakistan

Abstract: The current study was conducted from March 2021 to February 2022 in Thal desert and Trimmu barrage of District Jhang located in Punjab province of Pakistan to find out the diversity, abundance and distribution of birds. Point count method was used for Trimmu barrage and line transect method was used for the collection of data in Thal desert area. We recorded 31696 individuals belonging to 67 species of birds from two distinct types of habitat (Thal desert and Trimmu barrage) of District Jhang. Among all these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The site where the lowest number of birds was observed was Bhaiwal (n = 2), while the lowest number of species sighted was N = 2 at Islam Colony, Malik Bhaiwal, and Green Town. The lowest species diversity and bird abundance in these areas strongly suggested that anthropogenic activities in urban areas are collectively affecting avifauna due to land use, environmental pollution, and habitat loss [13,18]. Moreover, the availability of plenty of dietary resources, habitat suitability, a lower degree of urbanization, and natural habitat exploitation in the other parts of the study area provide a secure and flourishing habitat for bird populations and result in a rich ornithofaunal glimpse in the study area [7].…”
Section: Discussionmentioning
confidence: 99%
“…The site where the lowest number of birds was observed was Bhaiwal (n = 2), while the lowest number of species sighted was N = 2 at Islam Colony, Malik Bhaiwal, and Green Town. The lowest species diversity and bird abundance in these areas strongly suggested that anthropogenic activities in urban areas are collectively affecting avifauna due to land use, environmental pollution, and habitat loss [13,18]. Moreover, the availability of plenty of dietary resources, habitat suitability, a lower degree of urbanization, and natural habitat exploitation in the other parts of the study area provide a secure and flourishing habitat for bird populations and result in a rich ornithofaunal glimpse in the study area [7].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 31,696 individuals from sixty-seven species were observed during the duration of this study, thirty-nine of whom were residents: eighteen were winter visitors, nine were summer breeders, and one passage migrant species was the Terek sandpiper. Both study areas are diverse, but the Trimmu Berrage is more diverse, with H' = 3.139846, and the Thal Desert is less diverse, with H' = 3.037615 (Zaman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these, various anonymous sources helped in the identification of the species. Identification was also performed by studying the available literature in research papers (Ali et al, 1983;Grimmett et al, 2008;Altaf et al, 2013;Altaf, 2016;Altaf et al, 2018;Zaman et al, 2022).…”
Section: Identificationmentioning
confidence: 99%